Environmental Communication - A Journal of Nature and Culture - Environmental Communication - A Journal of Nature and Culture (Taylor & Francis, 2026)
IECA members can subscribe to Environmental Communication at a discounted rate. To become an IECA member, please visit https://theieca.org/membership. As the flagship journal of the International Environmental Communication Association, Environmental Communication is a premiere international and interdisciplinary publishing outlet for original research on the ways communication matters to ecological relations and vice versa. The journal is intended for scholars, students, and broadly engaged audiences attuned to the ethical stakes of environmental communication.
FI 0.92
Q1
Keywords: Geography; Planning; Urban & Environment; Ciencia ambiental; Comunicación; Acuerdos transformativos; Transformative agreements; Relaciones ecológicas; Etica; Ecología